Analisis Konstruksi Hukum Tindak Pidana Pembunuhan Berencana dalam Tahap Pra Ajudikasi - Muhammad Alief Wedar Murdyatna (Jurnal Hukum Lex Generalis, 2025)
Premeditated murder is a criminal act with the highest degree of intent, characterized by careful planning before execution. In the pre-adjudication stage, investigators play an essential role in constructing the legal framework to ensure that criminal acts meet juridical elements. The study found that the legal construction process often faces challenges in proving premeditation and limited evidence. The conclusion highlights the importance of investigator professionalism, in-depth analysis of legal elements, and effective coordination in establishing an objective and fair legal construction.